Application of Finite Element Modelling to Lightweight Aggregate (LECA) Column-Raft - Zukri, Azhani (International Journal of Integrated Engineering, 2019)
With the evolution of computer technology, many numerical software such as PLAXIS, FLAC, and ABACUS have been developed to solve complicated geotechnical problems in two or three-dimensional space. Finite element modeling can be easily applied to the treated soft soil with soil replacement or granular raft method, since the computer codes is able to solve complex problems like soil-structure interactions, seepage, and soil dynamic. In addition, the finite element analysis can be conducted rapidly and at relatively low cost. Soil replacement technique is the simplest and the oldest ground improvement method to improve the soft soils underneath light structures by replacing weak soil (e.g. soft clay and organic soils) with more competent materials such as sand, gravel or other suitable granular materials. The behavior of treated soils in terms of settlement and bearing capacity can be analyzed with finite element method. However, finite element analysis requires several preliminary checks to ensure the accuracy of the result. The use of finite element for geotechnical analysis requires consideration of the material model, mesh configuration and boundary conditions, type of analysis depending on objective of the research and time available. This paper focuses on the finite element modelling methodology developed to analyze the behavior of soft clay improved by Lightweight Expanded Clay Aggregate (LECA). LECA is known as common lightweight materials that have been applied successfully in civil engineering works where weight is an issue because by replacing the soft soils with this material, it can help to reduce dead loads and lateral forces by more than half. Mohr-Coulomb constitutive model has been selected to represent the behavior of LECA granular material in numerical analysis. While, the nonlinear behavior of soft soil (Kaolin Clay) is modelled with Soil Hardening constitutive model. In this paper, the validation methods that can be used to verify the numerical analysis is discussed. It is hope that this paper can be a useful guideline for young researcher in performing finite element modelling to simulate foundations supported by lightweight aggregate.